New bedrock map of Dome C, Antarctica, and morphostructural interpretation of the area - A. Forieri; A. Bini; TABACCO, IGNAZIO; L. Zuccoli; A. Zirizzotti; F. Remy (Annals of Glaciology, 2004)
A new bedrock map of the Dome C area is presented. The map, based on all radar data collected during Italian Antarctic Expeditions in 1995, 1997, 1999 and 2001, shows good agreement with the previous one. The Dome C plateau, along with some valleys and ridges, are clearly distinguished. The plateau, which develops at three different altimetric levels, is characterised by hills and closed depressions. Its morphology could be defined as a basin-and-range landscape: there are no visible features which can be ascribed to glacial erosion or deposition. The major valley is 15 km large and 500 m deep; its axis is parallel to that of other valleys and ridges in the plateau. The valley bottom is not flat, but contains a saddle in its centre. The morphology of the major valley could be considered a relict one which was not modified by the overlying ice cap. Two big ridges, characterised by hills, saddles and depressions, lie near the boundaries of the area. The map can also be used to recalculate ice thickness below the EPICA borehole. The new thickness is 3300 m, i.e. 50 m greater than the previous one, with several implications for the expected palaeoclimate record from the ice core.